Sensors and Systems for Indoor Positioning - Carotenuto, Riccardo; Merenda, Massimo; Iero, Demetrio (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint is a reprint of the articles that appeared in Sensors' (MDPI) Special Issue on "Sensors and Systems for Indoor Positioning". The published original contributions focused on systems and technologies to enable indoor applications.